Regional measurement of the hotel sector development of a tourist destination (on the example of Odessa region, Ukraine) - Балджи, Марина Дмитрівна; Baldzhy, Maryna D.; Nezdoyminov, Sergii G.; Нездоймінов, С. Г.; Kniazhkovska, Hanna O.; Княжковська, Г. О. (My University, 2021)
In the conditions of transformation of the national economy and intensification of competition in the regional tourist markets, Ukrainian hotel business enterprises have an important problem related to increasing the efficiency of filling hotel places and attracting tourist flows. One of the ways to solve this problem is to form a management measures based on forecasting the length of stay of tourists in accommodation facilities, load levels of hotel enterprises in tourist destinations of Ukraine, planning the production of competitive hotel services that can meet the needs of foreign and domestic consumers, market demand. This problem is especially important in the context of overcoming the effects of the global COVID-19 pandemic. The purpose of the article is to identify trends in the hotel business in the tourist regions of Ukraine and outline the prospects that can be realized in post-crisis conditions. The study used a statistical method of trend analysis of the dynamics of the duration of tourists in hotels, which aims at the establishing patterns of changes in the levels of the studied indicators over time, to identify the main trend of this phenomenon. The example of Odessa region proved that the evaluation of the hotel business areas are the basis for predicting spatial and temporal relationships in the regional economy for the development of hotel business in other tourist destinations, increase their competitiveness and improve the marketing of tourist flows. According to the calculations, the annual decrease in the length of stay of tourists for the period 2021-2022 in hotel establishments of the Odessa region is forecasted. The experience of experimental verification of the proposed approach to forecasting the length of stay of tourists in hotel establishments shows that the proposed research methods can form modern tools for diagnosing the current state of regional markets for hotel services and making management decisions.

В умовах трансформації національної економіки та загострення конкуренції на регіональних туристичних ринках, українські підприємства сфери гостинності мають важливу проблему, пов’язану з підвищенням ефективності завантаження готельних місць та приваблення туристичних потоків. Одним із шляхів вирішення цієї проблеми, автори вважають формування заходів управління на основі прогнозування тривалості перебування туристів в засобах розміщення, рівнів завантаження підприємств готельної сфери в туристичних дестинаціях України, планування виробництва конкурентоспроможних готельних послуг, які зможуть задовольнити потреби іноземних та вітчизняних споживачів, оперативно реагуючи на ринковий попит. Ця проблема набуває особливого значення в умовах подолання наслідків світової пандемії COVID-19. У статті проаналізовано тенденції розвитку сектору гостинності в туристичних дестинаціях України та запропоновано заходи, які можливо реалізувати у посткризових умовах діяльності підприємств галузі. Для дослідження був використаний статистичний метод трендового аналізу рядів динаміки тривалості перебування туристів в готелях, який спрямовано на встановлення закономірностей змін рівнів досліджуваних показників у часі, виявленні основної тенденції (тренда) розвитку цього явища. На прикладі Одеського регіону доведено, що оцінка діяльності підприємств готельного сектору є основою для прогнозування просторово-часових зв›язків в регіональній економіки щодо розвитку готельного бізнесу в інших туристичних дестинаціях, підвищення їх конкурентоспроможності та вдосконалення маркетингу туристичних потоків. За даними розрахунків прогнозується щорічне зменшення тривалості перебування туристів на період 2021-2022 років в готельних закладах Одеського регіону. Досвід експериментальної перевірки запропонованого підходу щодо прогнозування тривалості перебування туристів в готельних закладах показує, що запропоновані методи прогнозування можуть сформувати сучасні інструменти для діагностики стану регіональних ринків послуг гостинності та прийняття управлінських рішень.
Nezdoyminov S. G. Regional measurement of the hotel sector development of a tourist destination (on the example of Odessa region, Ukraine) / S. G. Nezdoyminov, M. D. Baldzhy, H. O. Kniazhkovska // Journ. Geol. Geograph. Geoecology . – 2021. – Vol. 30, №2. – Р. 344-354. https://doi.org/10.15421/112131
Keywords: hotel industry; tourist flow; forecasting; tourism; trend analysis; готельна індустрія; туристичний потік; прогнозування; туризм; трендовий аналіз; Research Subject Categories::SOCIAL SCIENCES